Drug-induced atypical hyperplasia enveloping salivary gland malignancy - Anjali Narwal; Virender Singh; Shashi Bala (Wolters Kluwer Medknow Publications, 2017)
Gingival enlargement is a very common side effect associated with the administration of several drugs, mainly anticonvulsants, calcium channel blockers (CCBs), and immunosuppressants. Amlodipine (a CCB) is a safe antihypertensive drug with a longer duration of action. Gingival enlargement induced by amlodipine is less prevalent among CCBs. Since the pathogenesis is not well understood, it is still a challenge for clinicians to diagnose and manage cases effectively. This case presents an atypical unilateral palatal gingival enlargement in a 61-year-old hypertensive female taking amlodipine. Difficulty for a pathologist in diagnosing in spite of repeated sample submission from the lesion and repeated failure for the operator to reach the underlying pathology due to amlodipine-induced hyperplasia have also been discussed in this case report.